A note on demand elasticities for energy imports - Reilly, Barry (Economic & Social Studies, 1986)
Annual Irish data on fuel imports are used to estimate inter-fuel substitution models. Both a four- and a three-input classification are employed in the estimation of a translog cost function. Restrictions implied by neo-classical production theory are imposed and statistically tested. The concavity and monotonicity conditions of the cost functions are also examined. Both models reject the neo-classical restrictions and their performances with regard to concavity and monotonicity conditions are mixed. Both cross- and own-price elasticities of demand for the fuel imports are also reported.
Keywords: Fuel imports - Ireland; Energy - Ireland